A different side of the COVID-19 pandemic - Lúcia Tavares; Paula Vagos; Ana Xavier (Psychologica, 2024)
The present study investigated the nature and meaning of the experiences of older adults who lived through the SARS-CoV-2/COVID-19 pandemic and the lockdown periods in Portugal. Narrative Research was used to explore the lived stories of two community-resident female older adults, recruited through convenience sampling. Data was collected through a semi-structured interview and thematically analyzed. Participants’ testimonies revealed a somewhat positive experience and no overwhelming difficulties were expressed. A positive and close relationship with family and personality traits such as optimism and hope emerged as the main coping strategies and resources to overcome challenges. Participants’ stories also highlighted constructs still scarcely studied among older adults: acceptance, self-compassion, and event centrality. Our findings, therefore, highlight the importance of acknowledging the idiosyncrasies of this population, rather than envisioning them as a homogenous at-risk group. Future research should use qualitative methodologies to give voice to older adults with different life stories.